Is emotional eating associated with behavioral traits and Mediterranean diet in children? A cross-sectional study - Alessandra Buja; Mariagiovanna Manfredi; Chiara Zampieri; Anil Minnicelli; Roberta Bolda; Filippo Brocadello; Maura Gatti; Tatjana Baldovin; Vincenzo Baldo (BMC, 2022)
Abstract Background Stress and negative emotions may impact on appetite, inducing some individuals to eat less and others to eat more. This behavior has been implicated in the onset of bodyweight problems and eating disorders in childhood. The aim of our study is to evaluate factors potentially associated with emotional eating in children. Methods The present cross-sectional study derives from a survey conducted in 2021 on 8-9 years old children attending 11 primary schools. A questionnaire was administered that contained multiple-choice items relating to the children and their mothers, and touching on all the factors thought to be associated with emotional eating as behavioral traits or adherence to Mediterranean diet. A multivariable logistic regression was performed to test the association. Results Emotional undereating was positively associated with emotional symptoms (OR 1.72; 95% CI 1.11-2.67); emotional overeating was positively associated with both emotional symptoms (OR 2.01; 95% CI 1.29-3.13) and hyperactivity (OR 2.80; 95% CI 1.59-4.92), and inversely associated with peer problems (OR 0.50; 95% CI 0.25-0.99). Emotional undereating was also positively associated with the number of siblings (OR 1.50; 95% CI 1.03-2.18), and inversely associated with a good adherence to the Mediterranean diet (OR 0.25; 95% CI 0.08-0.84). Conclusions The study found children's emotional eating associated with both dietary patterns and behavioral traits (in particular emotional symptoms, hyperactivity and peer problems). It could be useful to improve parents' awareness so that they can anticipate and pay more attention to this issue. Adherence to the Mediterranean diet should also be reinforced, by means of health promotion interventions at school, for example.